Potential anti-inflammatory effects of Psidium guajava L.: A review - souri, M. Sofyan; Oktavia, Sri; ifora, Ifora (Asian Journal of Pharmaceutical Research and Development, 2021)
Inﬂammation is a defence mechanism of a body against foreign substances. However, Inﬂammation also plays a key role in diseases such as diabetes, asthma, cardiovascular diseases, and cancer. Increasing scientiﬁc evidence has shown that fruits, vegetables, and legumes can have anti-inﬂammatory properties. This paper aims to provide recent studies on the anti-inflammatory properties of Psidium guajava L. A review was conducted on the studies of Psidium guajava L. anti-inflammatory properties performed during the past 10 years with the literature databases such as Pub Med, Science Direct, Google Scholar. Based on our eligibility criteria, a total of ten studies were included in this paper. The studies suggest that the anti-inflammatory activity of Psidium guajava occurs mainly through inhibition of PGE2, COX-2, NO, iNOS, ERK1/2, leukocyte cell migration, and suppression of edema, paw withdrawal latency as well as exhibited a membrane stabilization effect. This review has demonstrated the importance of Psidium guajava L. as a natural anti-inflammatory potential.